Investigating the Learners Profile of EFL Intermediate Speakers in 21st Century : A Case of Senior High School Students - Fauziyah, Jihan; Nafi'a, Ilman; Priajana, Nana (Foreign Language Instruction Probe, 2023)
This descriptive research aimed to analyze and describe the learners profile of Senior High School students at A Private Senior High School Cirebon in the academic 2022/2023. The subject of this study is the tenth grade students of Senior High School Cirebon. There were 4 students and 1 English teacher who were choosen as the subject of the study. Interview and literature review technique was applied in determining the subject. In order to collect the data for this study, the interviewed by face to face directly to find out how many characteristics Learners Profile their have in 21st century and find out the factors students have to make them successful as English students in 21st century. The research finding show that students get six characteristics of Learners Profile such as students have critical thinking, collaboration, a good communication, have creativity skill, have innovation think and their have own self-direction. To be a successfull English students must have grow a sense of motivation within yourself, have supportive learning community surround them and students uses media technology in learning English.